Materials science and technology :a comprehensive treatment /. Volume 10B, Nuclear Materials Part II/ edited by R.W. Cahn, P. Haasen, E.J. Kramer; Vol.ed. : Brian R. T. Frost - Frost, Brian R. T.
Vol. 10B. Nuclear Materials Part II.- 1993.